Censorship and Magic Tricks in Inter-War Britain - Lisa Z. Sigel (Revue LISA)
This paper demonstrates that between World War One and World War Two, the British state censored a variety of media including books, magazines, postcards, and films as well as engaging in public trials of obscene books that generated enormous publicity. Despite all of this, the British state denied that it censored and was largely successful at concealing its own practices. This paper documents the ways that the British state concealed the mechanisms of censorship and considers why these strategies became necessary when in previous decades the state had censored as a matter of course.